Extraction of K2CO3 from empty palm fruit bunch ash and properties analysis - Cindi Pakpahan; Susila Arita; Tuti Indah Sari; Leily Nurul Komariah; Fitri Hadiah; Nino Renaldi (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
Empty oil palm fruit bunches (EPFB) are the largest solid waste generated from palm oil mills. Accounting for 21-23 % of the total fresh fruit bunches. EFB ash contains K (Potassium) which can be recovered as K2CO3 through extraction. This research aims to recover K2CO3 from empty oil palm fruit bunches (EPFB) as a catalyst raw material because it is alkaline using the K2CO3 extraction method from the ash of empty oil palm fruit bunches (EPFB), which begins with a combustion process at a temperature of 700 oC to obtain ash. Ash extraction was carried out in 2 stages using water as a solvent. The K2CO3 yield from empty palm fruit bunch ash reached 57.28 %. The alkalinity test showed that the K2CO3 content in the solid extract reached 85.91 %. The properties of the ash and K2CO3 produced were analyzed using XRF, XRD and FTIR. The results of XRF analysis show that the potassium content in the ash contains the element K (potassium) which is quite large, namely 71.24 % and after extraction the purity of potassium oxide reaches 97.08 %. XRD analysis of the results of the synthesis of potassium carbonate from empty oil palm fruit bunches showed that the intensity of the material beam was obtained in a 2ϴ pattern which was lower than the intensity pattern of pure potassium carbonate. The results of FTIR analysis show that the spectrum of carbonate ions from the EPFB C-O bend is visible at 1359,879 and 700.75 cm-1 and these results are similaire to the pure carbonate ion vibration mode.